PENGARUH PERAN AUDIT INTERNAL TERHADAP PENCEGAHAN KECURANGAN (Studi Empiris Pada Perbankan di Pekanbaru) - Theresa Festi T; Andreas '; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research was to analyse about the influance of internal audit role consist of independence, professional proficiency, scope of work, performance of audit work, and management of internal auditing department toward fraud prevention. Total respondent which used in this research ware 51 respondents (85 %) .The samples in this research was internal control system and internal auditor whose work in branch bank’s Pekanbaru. This research was used survey methods which used quisioner instrument. The analyzing method was Simple Linier Regression methods. The result of the study indicated the internal audit role influenced toward fraud prevention . It meant that the internal audit role was better, as result the fraud prevention became increasing. The coefficient of determination (R2) in this research were 0.467. It meant that 46,7% fraud prevention was influenced by the internal audit role.Keywords : The Internal Audit Role, Prevention of fraud